2014
DOI: 10.1093/mp/ssu055
|View full text |Cite
|
Sign up to set email alerts
|

LSCHL4 from Japonica Cultivar, Which Is Allelic to NAL1 , Increases Yield of Indica Super Rice 93-11

Abstract: SUMMARYThe basic premise of high yield in rice is to improve leaf photosynthetic efficiency, and coordinate the source–sink relationship in rice plants. The quantitative trait loci (QTLs) qLSCHL4, japonica NAL1 allele from Nipponbare has a pleiotropic function, effectively increased leaf chlorophyll content, enlarged flag leaf size, and enhanced the yield of indica rice cultivar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 31 publications
8
128
0
2
Order By: Relevance
“…In addition to the increase in WFL and the number of vascular bundles, Nal1 increased the total number of spikelets per panicle, root dry weight, and the rate of filled grains (Fujita et al 2013). Improvements to the panicle, such as increased panicle length, more spikelets per panicle, and more secondary branches per panicle, were also observed after introducing the H-type allele (Zhang et al 2014). Since NAL1 is expressed in the culm, coleoptile, crown root, lateral root, and panicles (Qi et al 2008;Fujita et al 2013;Jiang et al 2015), its regulation of the cell cycle and cell division in these tissues likely explains the pleiotropic effects of the Nal1 mutation.…”
Section: Products Of the Malfunctional H 233 -Type Allele Still Regulmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition to the increase in WFL and the number of vascular bundles, Nal1 increased the total number of spikelets per panicle, root dry weight, and the rate of filled grains (Fujita et al 2013). Improvements to the panicle, such as increased panicle length, more spikelets per panicle, and more secondary branches per panicle, were also observed after introducing the H-type allele (Zhang et al 2014). Since NAL1 is expressed in the culm, coleoptile, crown root, lateral root, and panicles (Qi et al 2008;Fujita et al 2013;Jiang et al 2015), its regulation of the cell cycle and cell division in these tissues likely explains the pleiotropic effects of the Nal1 mutation.…”
Section: Products Of the Malfunctional H 233 -Type Allele Still Regulmentioning
confidence: 93%
“…In Koshihikari (type VI9), only 20% of NAL1 transcripts contained no retrotransposon, and a NAL1 protein the same size as that encoded by the R-type allele was synthesized (Takai et al 2013). Furthermore, it was shown that NAL1 expression was significantly higher in Nipponbare (type IV9) than in 93-11 (type I), although the expression level was shown to vary among developmental stages (Zhang et al 2014). Overexpression of the Nipponbare allele in Nipponbare increased FWL and LWL through increasing the distance between vascular bundles (Zhang et al 2014), indicating that the NAL1 transcript level is an important factor in leaf morphology.…”
Section: Amino Acid Change In Nal1 Is Important For Increased Wflmentioning
confidence: 99%
See 3 more Smart Citations